Barriers to Building Relationships in Counseling - Lika Widiawati; Mudjiran; Yeni Karneli (Journal Of Psychology, Counseling And Education, 2024)
This study explores the obstacles in the counseling process, specifically transference, countertransference, and resistance. Utilizing a library research method, the study analyzes existing concepts related to classroom management. Transference involves clients projecting feelings onto the counselor, which can be positive or negative and needs proper management to build trust. Countertransference occurs when therapists project their feelings onto clients, requiring introspection and supervision to avoid bias. Resistance involves clients' reluctance to open up or accept help, often due to mistrust or past experiences. Effective strategies to overcome these barriers include building trust through empathy, understanding, and confidentiality.